2015
DOI: 10.5798/diclemedj.0921.2015.02.0548
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of very low birth weight infants in the neonatal intensive care unit of a university hospital

Abstract: Şubat 2007 ile Şubat 2013 tarihleri arasında Fatih Üniversitesi Hastanesi yenidoğan yoğun bakım ünitesinde takip edilen doğum ağırlıkları 1500gr ve altı bebeklerin hastalık ve ölüm oranlarını belirlemek amacıyla hastalar retrospektif olarak incelendi. Yöntemler: Çalışma doğum kilosu 1000 gram ve daha az (31 bebek), 1001-1500 gram arası (41 bebek) olarak ikiye bölünen 72 prematüre bebek ile yapılmıştır. Bu bebeklerin verileri dosyalardan kaydedilip, istatiksel olarak değerlendirildi. Bebeklerin doğum ağırlıklar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Assisted reproductive techniques are used more commonly by the couples who want to have children. Assisted reproductive techniques increase the risk of low birth weight, preterm birth, being small for gestational age and admission to NICU 22 , which are major risk factors for ROP 23 25 . We also detected a significant relation between assisted reproduction and ROP, however our results showed that assisted reproduction decreased the incidence of any-stage ROP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assisted reproductive techniques are used more commonly by the couples who want to have children. Assisted reproductive techniques increase the risk of low birth weight, preterm birth, being small for gestational age and admission to NICU 22 , which are major risk factors for ROP 23 25 . We also detected a significant relation between assisted reproduction and ROP, however our results showed that assisted reproduction decreased the incidence of any-stage ROP.…”
Section: Resultsmentioning
confidence: 99%
“…birth, being small for gestational age and admission to NICU22 , which are major risk factors for ROP23 . The effects of assisted reproduction on the development of ROP have been studied previously.Barker et al couldn't find an association between assisted reproduction and ROP incidence 24 .…”
mentioning
confidence: 99%